The Types of Injury, Regions and Frequency in Athletes Participating Universities Taekwondo Championchip - Ekrem Boyalı; Süleyman Patlar; Murat Ergin; Ali Osman Kıvrak; Tayyar Karadağ; Hasan Yıldız; Ali Kemal Boztaş; Süha Gündoğdu (Türk Spor ve Egzersiz Dergisi)
This study aims to determine the rates of injuries, the types of injuries and what part of the body is mostly injured in professional taekwondo sportsmen during competitions. This study involves 287 sportsmen participated in the interuniversity Taekwando championship in Ordu. Injuries during a match of the championship was determined  by a team. The characteristics  and types of injuries, the sportsmen’s verbal expressions were registered by a pre-determined team, and it was mentioned about how these injuries occurred, in which part of the body the injuries were seen. Among 287 sportsmen in this study, 178 sportsmen were male, 109 ones were female. 46 universities took part in this championship. The championship lasted three days and total 271 competitions were done. 539 injuries were determined in total. The mostly seen type of injury was hematoma (43%), the mostly injured part was in lower extremities 416 (77%), most of the injuries were ones seen in defense (36%). No injuries were not observed in neck, shoulder, spine or trunk and cerebral injuries were not also observed. As a result of the study, it was explained that most of the injuries seen in the taekwondo competitions did not require the medical intervention and the lower extremities were mostly injured in these competitions. In the light of these findings, it could be said that these parts be protected during the competitions and the defense techniques be different.